Taking life imprisonment seriously in national and international law : In National and International Law. - Van Zyl Smit, D. (BRILL, 2002)
Life imprisonment is a complex and drastic penal sanction. It gives the State the power to curtail the liberty of offenders for the rest of their lives. In many jurisdictions life imprisonment is the ultimate sanction for the most serious crimes. It is frequently touted as an alternative to the death penalty. At the same time, life imprisonment is often imposed as a preventive measure, where the offence alone does not justify using the ultimate sanction in the penal arsenal. The complexity of life imprisonment is frequently overlooked. Often it is assumed that it is not as drastic as it sounds.